Does Psychological Contract Violation Moderate the Impact of Severity and Recovery Satisfaction on Boycott? An Analysis of Halal Violation - Omar, NA; Nazri, MA; Mohd-Ramly, S; Zainol, Z (Routledge Journals, Taylor & Francis Ltd, 2024)
Indexed by WOS/SCOPUS